Analisis Kesulitan Siswa Berdasarkan Kemampuan Pemahaman Matematis dalam Menyelesaikan Soal Cerita Pada Materi FPB dan KPK - Fioni M. Y. Kase; Rike D. H. Nesti; Patrisia P. Senid; Maria E. Senia; Rambu Djawa (Universitas Nusa Cendana, 2021)
This research aims to analyze the difficulties of students of 4th gradersin GMIT Oenesu Elementary School, Kupang, NTT based on their mathematical understanding ability in solving story problems in FPB and KPK materials. The research method used is qualitative descriptive by describing written answers and interviews to students' mathematical comprehension abilities. The subjects in this study were students of 4th gradersin GMIT Oenesu Elementary School, Kupang, NTT which numbered 10 people. Based on the test results, 3 students from low, moderate, and high-skilled subjects were taken. The instruments used are written tests and interviews. The results showed that 8 out of 10 students had difficulty in solving story problems in FPB and KPK materials based on their mathematical understanding skills. It was also found that the difficulties experienced by students were related to (1) Difficulty restating the concept, characterized by students not yet understanding the problems experienced by S1, (2) Difficulty classifying objects based on the fulfillment or absence of the requirements that make up the concept, characterized by students unable to write down what is known and asked from the questions experienced by S1, (3) Difficulty applying the concept of algorithms, characterized by student errors in completing FPB and KPK experienced by S1 and S2, and (4) Difficulty associating various concepts, characterized by students have not been able to determine what calculation operations can be used next to solve the problems experienced by S1, S2 and S3. In addition, difficulty in associating various concepts is the dominant difficulty carried out by students.